Scaling Down: A Modest Proposal for Practice-based Policy Research in Teaching - Frederick Erickson (Arizona State University, 2014)
This proposal addresses the assumptions underlying the "Science Wars" about the purpose of educational research. The author proposes a more modest "Lake Woebegon" approach to school reform that supports long-term professional education, a shift away from "Best Practices" to "Pretty Good Practices," low fidelity implementation of interventions, and the importance of local context. Action research is presented as one possible qualitative approach for conducting "practice-based research."